Association Between sTREM2, an Immune Biomarker of Microglial Activation, and Aging-Related Brain Volume Changes in Community-Dwelling Older Adults: A 7-Year Follow-Up Study - Orihashi, Ryuzo; Mizoguchi, Yoshito; Imamura, Yoshiomi; Yamada, Shigeto; Monji, Akira (Frontiers in Aging Neuroscience, 2021)
Background This study aimed to investigate the association between serum levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2), a soluble form of an innate immune receptor expressed on the microglia, and brain volume in older adults. Methods The survey was conducted twice in Kurokawa-cho, Imari, Saga Prefecture, Japan, among people aged 65 years and older. We collected data from 596 residents. Serum sTREM2 level measurements, brain MRI, Mini-Mental State Examination (MMSE), and clinical dementia rating (CDR) were performed at Time 1 (2009–2011). Follow-up brain MRI, MMSE, and CDR were performed at Time 2 (2016–2017). The interval between Time 1 and Time 2 was approximately 7 years. Sixty-nine participants (16 men, mean age 72.69 ± 3.18 years; 53 women, mean age 72.68 ± 4.64 years) completed this study. We analyzed the correlation between serum sTREM2 levels (Time 1) and brain volume (Time 1, Time 2, and Time 1–Time 2 difference) using voxel-based morphometry implemented with Statistical Parametric Mapping. Results Participants in this study had lower MMSE and higher CDR scores 7 years after the baseline evaluation. However, analyses at the cluster level by applying multiple comparison corrections (family wise error; P < 0.05) showed no correlation between serum sTREM2 levels and volume of different brain regions, either cross-sectional or longitudinal. Conclusion Serum sTREM2 level could not serve as an immune biomarker of aging-related volume changes in brain regions closely related to cognitive function in older adults aged 65 years and above.